Qualification Of Age Limits For Criminal Responcibility According To The Child Criminal Justice System And Indonesia Criminal Code - Kaluku, Julisa Aprilia; Kasim, Ramdhan; Moha, Mohamad Rivaldi; Badu, Lisnawaty Wadju (Universitas Widya Gama Malang, 2023)
The age limit for children is very important in juvenile criminal cases, because it is used to find out whether a person suspected of committing a crime is included in the category of a child or not. Limitation of the age of children, there is also diversity in various countries that regulate the age of children who can be punished. Some countries also provide a definition of a person being said to be a child or an adult in terms of age and activity or ability to think. The approach method in this study uses an approach to legislation (statue approach), fact approach, case approach and analysis of legal concepts. The results in this study are the non-uniformity of the qualifications for the age limit of children between one law and another, giving rise to various existing legal conflicts regarding the limits of children's responsibility. According to the Criminal Code Number 1 of 2023 in article 40, it states that criminal liability cannot be imposed on children who are not yet 12 (twelve) years old at the time of committing the crime, while in Law Number 11 of 2012 it states that children who are in conflict with The law hereinafter referred to as a child is a child who is 12 (twelve) years old but not yet 18 (eighteen) years old who is suspected of committing a crime.